Membangun Komunitas Rumah Tahfidz Anak Untuk Percepatan Program Magrib Mengaji - Afnita, Nora; Makki, Ismail (Proceedings of Annual Conference on Community Engagement, 2018)
The aim of the research was to construct a tahfidz house for children community in Padusunan Pariaman and to develop a tahfidz method of remembering one Juz during 10 days on the acceleration of Magrib Mengaji Program as well as to synergize the role of tahfidz community for children to facilitate them in memorizing of the Qur’an easily. Method of this research used community based research with mix method analysis. Result of the research showed that this program was really important in the implementation of memorizing the Qur’an quickly with one juz completed for 10 days and have got success to accelerate the achievement of Magrib Mengaji Program in Pariaman with a lot of children who interest to enroll to Tahfidz house and having fun to reading and memorizing the Qur’an. This program has given a big impact to syiar of Islamic religion in Pariaman and graduate a lot of children love with al Qur’an. For local leader in Pariaman hopefully want to focus in following up this activity by continuing this program in the Grand Mosque of Pariaman at least twice a week, every Sunday and Thursday.